2019
DOI: 10.1017/s0144686x19000527
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of depression and burden among informal care-givers of people with dementia: a meta-analysis

Abstract: This meta-analysis examined the prevalence of depression and burden among informal caregivers of people with dementia (PwD) and compared the prevalence of depression between male and female, and spousal and non-spousal, caregivers. The quality of studies was evaluated and moderator variables explored. A search of six electronic databases (PsycARTICLES, PsycINFO, MEDLINE Complete, SCOPUS, Web of Science and ProQuest) was conducted from the first available date to the 31st October 2017. Inclusion criteria involv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
112
5
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 153 publications
(122 citation statements)
references
References 113 publications
4
112
5
1
Order By: Relevance
“…32 The overall pooled anxiety prevalence rate was 32.1% in the current study, which is comparable to the pooled estimate of 31.2% for the prevalence of depression obtained by the recent review conducted by Collins and Kishita. 54 Previous studies reported that the prevalence rate of anxiety disorders in older people as measured by diagnostic tools or self-report symptom measures to be 1.2% to 14%. 55 The recent meta-analysis on global prevalence of anxiety symptoms among carers of stroke survivor estimated the prevalence rate at 21.4%.…”
Section: Discussionmentioning
confidence: 99%
“…32 The overall pooled anxiety prevalence rate was 32.1% in the current study, which is comparable to the pooled estimate of 31.2% for the prevalence of depression obtained by the recent review conducted by Collins and Kishita. 54 Previous studies reported that the prevalence rate of anxiety disorders in older people as measured by diagnostic tools or self-report symptom measures to be 1.2% to 14%. 55 The recent meta-analysis on global prevalence of anxiety symptoms among carers of stroke survivor estimated the prevalence rate at 21.4%.…”
Section: Discussionmentioning
confidence: 99%
“…[358][359][360][361][362] • The prevalence of depression is higher among dementia caregivers (30% to 40%) than other caregivers, such as those who provide help to individuals with schizophrenia (20%) or stroke (19%). [362][363][364][365] • In a meta-analysis, the type of relationship was the strongest predictor of caregiver depression; caregivers of spouses had two and a half times higher odds of having depression than caregivers of people who were not spouses. 362 • The prevalence of anxiety among dementia caregivers is 44%, which is higher than among caregivers of people with stroke (31%).…”
Section: Caregiver Emotional and Social Well-beingmentioning
confidence: 99%
“…Approximately 30% to 40% of family caregivers of people with dementia report depression, compared with 5% to 17% of non‐caregivers of similar ages 358‐362 The prevalence of depression is higher among dementia caregivers (30% to 40%) than other caregivers, such as those who provide help to individuals with schizophrenia (20%) or stroke (19%) 362‐365 In a meta‐analysis, the type of relationship was the strongest predictor of caregiver depression; caregivers of spouses had two and a half times higher odds of having depression than caregivers of people who were not spouses 362 …”
Section: Caregivingmentioning
confidence: 99%
“…However, an extensive body of research shows that caring for an older family member can also be a stressful and challenging experience . Across the extant literature, the prevalence of psychological distress (eg, depression, anxiety, and stress), burden, loneliness, isolation, chronic conditions (eg, cardiovascular disease, diabetes, and osteoporosis), impaired immunity and altered stress hormones, and disability is consistently higher in carers than noncaregivers, and this difference is most pronounced for carers of people with dementia . Alongside this, there are often adverse financial consequences with a reduced ability to participate in the paid workforce placing many carers under day‐to‐day economic strain and inhibiting longer‐term financial planning, such as saving for retirement .…”
Section: Family Caring In An Aging Populationmentioning
confidence: 99%
“…12 Across the extant literature, the prevalence of psychological distress (eg, depression, anxiety, and stress), burden, loneliness, isolation, chronic conditions (eg, cardiovascular disease, diabetes, and osteoporosis), impaired immunity and altered stress hormones, and disability is consistently higher in carers than noncaregivers, [13][14][15] and this difference is most pronounced for carers of people with dementia. 16 Alongside this, there are often adverse financial consequences with a reduced ability to participate in the paid workforce placing many carers under day-to-day economic strain and inhibiting longer-term financial planning, such as saving for retirement. 6,12,13 The potential implications of these effects are farreaching for some carers, as poor carer mental health is a known risk factor for suicidal ideation in family carers of people with dementia, 17 increased neglect and abuse of older adults, 18 and increased mortality of people with neurodegenerative diseases.…”
Section: Family Caring In An Aging Populationmentioning
confidence: 99%